Kesesuaian Konsep Wellnest Tourism Pada Perkembangan Pemandian Aia Angek Padang Ganting Di Kota Batusangkar - Frily, Amanda Faradhita; Fasandra, Fernando (Journal of Tourism Sciences, Technology and Industry, 2024)
The concept of Wellness Tourism involves engaging in tourism activities while prioritizing health and wellness. The components of the Wellness Tourism concept that will be examined include the utilization of tourist attractions as tourist attractions, tourist motivation, tourism service facilities, accessibility of tourist areas, and the institutional management of tourist sites. In line with the activities and concept of Wellness Tourism, where hot springs are one of the activities, the Aia Angek Hot Springs is a tourist site with a natural spring source. Data collection was conducted through field observation, literature study, questionnaires, and interviews. This research uses quantitative data analysis methods, which include descriptive analysis and scoring analysis. The Aia Angek Padang Ganting hot springs received a score of 77,8 %, indicating that the Wellness Tourism concept in the development of Aia Angek hot springs is appropriate, but there are components that received less favorable results and require improvement and attention from the management. Keywords: Wellness Tourism, Health Tourism, Hot Springs, Batusangkar